Hermeneutical Approach to Understanding Article 48 Paragraph (4) Of Law No. 10 Of 2016: Philosophy, Theology and Protection of Voter Rights in Indonesia - Rahmiati, Rahmiati; Nazwa Aulia, Svenska; Sendi, Sanjaya; Ghazza, Jaudat; Fasmadhy Deddi, Satiadharmanto (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
A hermeneutic approach to the judicial review of Article 48 Paragraph (4) of Law Number 10 of 2016 is employed to assess its alignment with the 1945 Constitution of the Republic of Indonesia and to analyze its impact on the constitutional rights of voters. This study uses hermeneutics as a tool to deeply understand the legal meaning and implications of the article, while also examining potential conflicts of interest that may arise from the provision, particularly involving political parties in the electoral process. The research method utilized is qualitative analysis with a normative approach to relevant regulations and Constitutional Court decisions, using a hermeneutic perspective that considers the context and comprehensive interpretation of the law. Data sources include legal documents, Constitutional Court decisions, and literature analyzes related to voters' constitutional rights and conflicts of interest. The findings of this study indicate that Article 48 Paragraph (4) of Law 10/2016 not only conflicts with constitutional principles but also creates opportunities for conflicts of interest among political parties. Therefore, a clearer and more precise interpretation through a hermeneutic approach is required to protect voters' rights and ensure the integrity of the electoral process.